Practice Summary of Antimicrobial Therapy for Commonly Encountered Conditions in the Neonatal Intensive Care Unit: A Canadian Perspective - Ting, Joseph Y.; Autmizguine, Julie; Dunn, Michael S.; Choudhury, Julie; Blackburn, Julie; Gupta-Bhatnagar, Shikha; Assen, Katrin; Emberley, Julie; Khan, Sarah; Leung, Jessica; Lin, Grace J.; Lu-Cleary, Destiny; et al. (Frontiers in Pediatrics, 2022)
Neonates are highly susceptible to infections owing to their immature cellular and humoral immune functions, as well the need for invasive devices. There is a wide practice variation in the choice and duration of antimicrobial treatment, even for relatively common conditions in the NICU, attributed to the lack of evidence-based guidelines. Early decisive treatment with broad-spectrum antimicrobials is the preferred clinical choice for treating sick infants with possible bacterial infection. Prolonged antimicrobial exposure among infants without clear indications has been associated with adverse neonatal outcomes and increased drug resistance. Herein, we review and summarize the best practices from the existing literature regarding antimicrobial use in commonly encountered conditions in neonates.